Maskulinisasi Ikan Nila Melalui Perendaman Larva pada Suhu 36 °c dan Kadar Residu 17a-metiltestosteron dalam Tubuh Ikan - Afpriyaningrum MD; Soelistyowati DT; Hardiantho D; Alimuddin Alimuddin; Zairin Jr M; Setiawati M (Journal Omni-Akuatika, 2016)
The residue of 17a-methyltestosterone (MT) in fish has been a concern related to food and the environment safety. This study aimed to determine sex ratio of Nile tilapia treated by MT immersion at 36 °C water temperature, and measure the level of testosterone in fish body. Three hundreds of ten-day-old post hatched larvae was immersed in one liter of water containing 2 mg MT, at 26 °C and 36 °C. Immersion was performed for 2 and 4 hours. The results showed that immersion at 36 °C and increasing immersion time increased male percentage. Higher male percentage was obtained in treatment 4 hours immersion at 36 °C (92.5% male) and the effective treatmen 4 hours immersion at room temperature. By ELISA method, testosterone level in MT treated fish decreased sharply to 88.2% at one month after immersion, and being the same as control without MT immersion. Thus, masculization in tilapia could be performed by MT immersion at 36 °C water temperature for 4 hours, and it is most likely that no MT residual in fish after one month post immersion. Keywords: Nile tilapia, sex reversal, temperature, 17a-methyltestosterone